Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahan di Indonesia Yang Bergerak di Sub Sektor Retail dan Trade, Healthy Care, Computer dan Service, dan Investment Company - Ong Yuliana (Business Accounting Review, 2015)
The objective of this research was to identify wheter there was an influence of Corporate Social Responsibility on the Firm Value measured by using Tobin’s q based on the Global Reporting Initiative standard. Sample was obtained from 130 companies during the periode of 2009-2013 in trading, service, and investment sectors. The result of this research shows ad that Corporate Social Responsibility has no significant Influence on the firm value. Similarly, the control variables, of Firm Size, Der, and Market Share, were also proven had have no significant Influence on the firm value.